2018
DOI: 10.22159/ajpcr.2018.v11i8.24743
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Dosage on Retention in Patients Methadone Maintenance Therapy Program for Maintenance Phase of H. Adam Malik Medan Central General Hospital

Abstract: Objective: This study aims to see the effect of methadone dose on patient retention in following the program.Materials and Methods: This study is a clinical study with cross-sectional study design. Data obtained from the patient’s medical record and patient’s primary data. The study was conducted at Methadone Clinic of H.Adam Malik Hospital Medan. Results: The number of research samples is injecting drug users who follow PTRM as many as 39 people. From a study of 39 patients, the percentage of male patients (1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…Retention is the length of time the patient in therapy, calculated from the first day the patient received methadone until he was discharged from therapy or until the end of the data collection limit. 12 The mean retention time of the patients was 769.63 days which was in the range of 53-2,478 days. Of the total 136 patients, 89 patients Various studies have shown an increase in patient outcomes at retention times of 1 year or more.…”
Section: Retentionmentioning
confidence: 88%
“…Retention is the length of time the patient in therapy, calculated from the first day the patient received methadone until he was discharged from therapy or until the end of the data collection limit. 12 The mean retention time of the patients was 769.63 days which was in the range of 53-2,478 days. Of the total 136 patients, 89 patients Various studies have shown an increase in patient outcomes at retention times of 1 year or more.…”
Section: Retentionmentioning
confidence: 88%